Isolation and identification of Salmonella spp. in raw milk from dairy herds in Colombia - Castañeda-Salazar, Rubiela; Pulido-Villamarín, Adriana del Pilar; Ángel-Rodríguez, Geraldine Lorena; Zafra-Alba, Camila Andrea; Oliver-Espinosa, Olimpo Juan (Brazilian Journal of Veterinary Research and Animal Science, 2021)
Salmonellosis is a foodborne disease (FBD) that affects public health and can cause death in people. Many outbreaks of Salmonellosis have been reported due to the contamination of raw milk and dairy products with the pathogen. To determine the prevalence of Salmonella spp. in milk samples from four dairy herds in the Sabana of Bogotá in 2017, 112 milk samples were taken directly from the mammary gland during milking. All milk samples were cultured and tested to isolate and identify Salmonella spp. using microbiological and molecular methods. Salmonella spp. prevalence of milk samples was found to be 20.5% (n=23). The main Salmonella serovars isolated were S. Newport (60.87%), S. Typhimurium (17.4%), S. Virchow, S. Bredeney, and S. Anatum (4.3% each one of the serovars). However, it was not possible to determine the Salmonella serotype in two isolates. The prevalence of Salmonella spp. in milk has not been studied extensively in Colombia. The 20.5% in the prevalence might be due to fact that the sample was taken directly from the mammary gland allowing a better chance of isolation by avoiding the dilutional effect of mixed milk from different cows in the buckets. This also suggests that the infection of the udder could have occurred by hematogenous dissemination or by milking machine contamination. This study highlights the need to implement measures to prevent contamination and reduce the problem in the herds, which will result in milk and dairy products with high standards of innocuity and quality and decrease the risk of foodborne illness.